Studi Karakteristik Kuat Tekan Beton Geopolimer Berbahan Dasar Abu Sekam Padi - Rani Adinda Meiliana; Sartika Nisumanti; Febryandi Nisumanti (Journal of Applied Civil Engineering and Infrastructure Technology, 2026)
Geopolymer concrete is an environmentally friendly alternative to conventional concrete because it has the potential to reduce carbon emissions. Rice husk ash, an agricultural waste, serves as a source of silica and alumina in the geopolymerization process. This study aims to determine the compressive strength value of geopolymer concrete in each variation and the use of alkali activator ratios between Na2SiO3 and NaOH with ratios of 1:2, 2:2, and 3:2. In the study of the compressive strength characteristics of engineering concrete, the experimental method was used. Based on the study of the compressive strength characteristics of geopolymer concrete made from rice husk ash, normal concrete at the age of 28 days has a compressive strength of 368 kg/cm2, while in the 1st geopolymer concrete at the age of 28 days, a compressive strength of 349 kg/cm2 is obtained. This shows that the compressive strength of the 1st geopolymer concrete has decreased by 5% from normal concrete, in the 2nd geopolymer concrete at the age of 28 days, a compressive strength value of 475 kg/cm2 was obtained, which means that the compressive strength of the 2nd geopolymer concrete has increased by 29% from the compressive strength of normal concrete. This study identified the optimal compressive strength of geopolymer concrete, specifically noting that the second geopolymer concrete reached a value of 475 kg/cm².